Customizable Templates for OutSystems Applications - Manteigas, Constança Maria Manso Ribeiro Amador (2022)
This dissertation addresses an extension of a metaprogramming mechanism in low-code platforms, specifically in the OutSystems platform. As proposed in the template language OSTRICH, model templates allow developers to reuse existing and thoroughly tested code fragments in a more productive and sound development process. Code templates help to overcome developer difficulties and lack of training. For instance, the development of professionally designed user interfaces is not a skill that is common amongst developers. Scenarios like specific synchronization algorithms are the other end of the spectrum for templates in OutSystems. The GOLEM project has the chief objective of providing mechanisms for automated programming. Such automation will make programming more accessible to a larger community of developers. This work is part of those efforts. To this end, our focus will be on developing and improving the template language OSTRICH that targets the OutSystems platform. It enables the creation of code fragments like screen templates, saving the user from the cumbersome task of repeatedly constructing code complex patterns. In OSTRICH, templates are instantiated by expanding their definition in the caller context to enable further customization of the resulting code. OSTRICH preserves the structure of the original model by expanding templates in place. However, expanding the template definition in place breaks the possibility of reapplying the template in the case of an update to a newer version or changing parameters. It requires the user to repeat all customization operations on top of a new instantiation of the template. Our purpose is to solve this issue by supporting customization operations that extend to all future template updates and new parameters. This way, the user will be saved from some erroneous trials, which could, eventually, push them to give up. We plan to evaluate our work using the benchmark template examples used previously to evaluate OSTRICH.